Sacrilege and the City in Sophocles’ Tragedies - Vicente Sánchez, Ana C. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper explores the lexical and semantic level of irreligious terminology in Greek Literature. A key term and a relevant author have been selected in order to illustrate the importance of the irreligious aspects in the society of the Classical Period. The adjective ὅσιος designates a religious respect in actions and attitudes towards the divinities and other human beings. Sophocles uses its privative form ἀνόσιος in contexts where such religious respect is lacking, with negative consequences for the polis.